2014
DOI: 10.1111/fcp.12062
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of effects of levobupivacaine injection to rabbit knee joint on histopathologic changes of joint cartilage tissue and changes of serum biochemical parameters

Abstract: The aim of this study is to evaluate the effects of intra-articular levobupivacaine on rabbit knee articular cartilage and certain biochemical parameters in the blood. A total of 24 New Zealand rabbits were included to study. Blood sampling was carried out in all animals on the first day, then the subjects were randomly allocated either to the control group (Group C, n = 9) or to the levobupivacaine group (Group L, n = 15). Group C underwent each two intra-articular injections of saline, 0.25 mL into the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is of great importance to investigate the histopathological adverse effects of such locally administered drugs, as well as their analgesic effects. Ozkaya et al [9] evaluated the intra-articular effects of levobupivacaine and reported that intra-articular levobupivacaine did not increase inflammation indicators and did not lead to significant histologic changes in rabbit articular cartilage. We also compared the short-and long-term histopathological effects of dexketoprofen trometamol on rabbit's knee joints on the 1st day, 2nd day and 10th day, and we did not detect any histopathological degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It is of great importance to investigate the histopathological adverse effects of such locally administered drugs, as well as their analgesic effects. Ozkaya et al [9] evaluated the intra-articular effects of levobupivacaine and reported that intra-articular levobupivacaine did not increase inflammation indicators and did not lead to significant histologic changes in rabbit articular cartilage. We also compared the short-and long-term histopathological effects of dexketoprofen trometamol on rabbit's knee joints on the 1st day, 2nd day and 10th day, and we did not detect any histopathological degradation.…”
Section: Discussionmentioning
confidence: 99%